Fake News and the 2017 Kenyan Elections. Issue 4 (1st October 2020) - Mutahi, Patrick; Kimari, Brian
Abstract: Similar to previous polls, the 2017 elections in Kenya were closely contested in all the seats. During the 2017 polls, however, social networking sites were widely employed, including in campaigns where candidates not only set up websites but also employed bloggers and social media managers to manage their social media accounts and constantly post their campaign messages. As this paper notes, while social media fostered access to important information on the elections, it was also used to spread fake news intended mainly to win over voters, create fear and alarm, and sometimes disparage some of the independent institutions that were managing the elections. Using data collected during and after the August 8, 2017 General Election and October 26, 2017 repeat presidential contest, this paper examines how fake news was used to advance different political agendas. It answers two main questions: What was the nature of the fake news during the 2017 elections? And, what were the implications of the spread of fake news in the 2017 elections? An examination of these issues will provide a deeper understanding of how fake news featured in Kenya's political discourse in the 2017 elections.